2006
DOI: 10.1074/jbc.m602221200
|View full text |Cite
|
Sign up to set email alerts
|

Erm/Thyroid Transcription Factor 1 Interactions Modulate Surfactant Protein C Transcription

Abstract: Expression of surfactant protein C (SP-C), which is restricted to alveolar type II epithelial cells of the adult lung, is critically dependent on thyroid transcription factor 1 (TTF-1). In the present study we have demonstrated that Erm, a member of the Ets family of transcription factors, is expressed in the distal lung epithelium during development and is also restricted to alveolar type II cells in the adult. Erm was up-regulated by fibroblast growth factors (FGFs) in culture, and blocking FGF signaling inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
(50 reference statements)
2
31
1
Order By: Relevance
“…All photomicrographs were taken at the same original magnification. has shown is up-regulated by Erm (Lin et al, 2006). Sftpc expression increases in late-gestation distal epithelium, when there is a concomitant decrease in Elf5 expression, suggesting that an absence of Elf5 in the distal epithelium may be needed for robust Sftpc expression.…”
Section: Su5402 Down-regulates Fgfsensitive Genes In the Lung Epitheliummentioning
confidence: 91%
See 3 more Smart Citations
“…All photomicrographs were taken at the same original magnification. has shown is up-regulated by Erm (Lin et al, 2006). Sftpc expression increases in late-gestation distal epithelium, when there is a concomitant decrease in Elf5 expression, suggesting that an absence of Elf5 in the distal epithelium may be needed for robust Sftpc expression.…”
Section: Su5402 Down-regulates Fgfsensitive Genes In the Lung Epitheliummentioning
confidence: 91%
“…Furthermore, studies in our laboratory have shown that Erm directly regulates Sftpc transcription by interacting with Ttf1 through its Ets domain (Lin et al, 2006).…”
Section: Su5402 Down-regulates Fgfsensitive Genes In the Lung Epitheliummentioning
confidence: 98%
See 2 more Smart Citations
“…The centralized homeodomain is known to bind to other transcription factors, including retinoic acid receptors (RARs) (Yan et al, 2001), zinc finger GATA transcription-6 (GATA-6) (Liu et al, 2002;Weidenfeld et al, 2002), and nuclear factor of activated T cells (NFAT) (Dave et al, 2004). Finally, the COOH-terminus functionally interacts with the DNA repair protein thymine DNA glycosylase (TDG) (Missero et al, 2001), other transcriptional coactivators such as p300 (Bachurski et al, 2003;Grasberger et al, 2005), SRC-3, SRC-2, BR22 (amino acid 6-206) (Yang et al, 2001;2003), poly(adenosine diphosphate-ribose) polymerase-1 (PARP-1), PARP-2 (Maeda et al, 2006), and other transcription factors such as nuclear factor κB (NF-κB) (Islam and Mendelson, 2006), signal transducers and activators of transcription 3 (STAT3) (Yan et al, 2002), Drosophila mothers against decapentaplegic 3 (SMAD3) (Li et al, 2002), nuclear factor I (NFI) (Missero et al, 2001), and ezrinradixin-moesin (ERM) (Lin et al, 2006).…”
Section: Structure Of the Nkx2-1 Gene And Protein And Its Biologicalmentioning
confidence: 99%